Maternal vitamin D levels during pregnancy and offspring schizophrenia - Sourander, Andre; Upadhyaya, Subina; Surcel, Heljä-Marja; Hinkka-Yli-Salomäki, Susanna; Cheslack-Postava, Keely; Silwal, Sanju; McKeague, Ian W.; Brown, Alan S. (Elsevier, 2025)
Background Findings from previous studies on maternal 25(OH)D levels during pregnancy and offspring schizophrenia are limited and inconsistent. Methods We used nationwide population-based register data with a nested case-control design to examine the association between maternal 25(OH)D levels during pregnancy and offspring schizophrenia. The cases of schizophrenia (n = 1145) were born from 1987 to 1997, and received a diagnosis of schizophrenia by 2017, and were matched with equal number of controls. A quantitative immunoassay was used to measure maternal 25(OH)D in archived maternal serum in the national biobank of the Finnish Maternity Cohort, collected during the first and early second trimesters. Conditional logistic regression models examined the association between maternal 25(OH)D levels and offspring schizophrenia. Results No significant association was found between log-transformed maternal 25(OH)D levels and schizophrenia in unadjusted (OR 0.96, 95 % CI 0.78–1.17, p = 0.69) or adjusted analyses (aOR 0.98, 95 % CI 0.79–1.22, p = 0.89). Analyses by quintiles also revealed no association between the lowest quintile of maternal 25(OH)D levels and schizophrenia (OR 1.09, 95 % CI 0.81–1.45, p = 0.55; aOR 1.06, 95 % CI 0.78–1.45, p = 0.71). Maternal 25(OH)D levels, measured in categories, either in deficient category (OR 1.07 (0.85–1.35), p = 0.52; aOR 1.05 (0.81–1.34), p = 0.88) or insufficient category (OR 1.13, 95 % CI 0.92–1.40, p = 0.23; aOR 1.13, 95 % CI 0.90–1.41, p = 0.27) were also not associated with offspring schizophrenia. Conclusions Maternal vitamin D levels in early pregnancy were not associated with offspring schizophrenia. Future studies measuring vitamin D during different stages of gestation are needed to draw firm conclusions.